(untitled) (International Journal of Engineering and Computer Science, 2017)
Mobile ad hoc networks (MANET) is a complex distributed systems that comprise wireless mobile nodes which, dynamically self organize into arbitrary Adhoc network topologies, allowing devices to seamlessly networked in areas with no preexisting communication infrastructure. The recent interest in the research community is to understand the capacity changes under delay constraints in mobile ad hoc networks. In this project, we are concentrating on capacity-delay scaling optimality for multicast traffic pattern for an i.i.d. mobility model in mobile ad hoc networks. With the assumption that n nodes move in a unit square, with each serving as a source that sends identical packets to k destinations, we propose four group schemes of which the achievable capacity and delay are analyzed: (1) Non-cooperative non-redundancy scheme, (2) Non-cooperative redundancy scheme, (3) Cooperative non-redundancy scheme, (4) Cooperative redundancy scheme. With intelligent cooperation scheme, each destination acts equivalently as relay and helps other destinations get more opportunities of receiving packets with capacity sacrificed. The project work is design and implement the following group schemes and to simulate using NS2. The results are will be compared with using algorithms and without using algorithms to show the increase in the performance of the proposed algorithm.